Treatment of popliteal cysts via arthroscopic enlargement of unidirectional valvular slits. Issue 5 (September 2015) - Ohishi, Tsuyoshi; Takahashi, Masaaki; Suzuki, Daisuke; Fujita, Tomotada; Yamamoto, Kazufumi; Ushirozako, Hiroki; Banno, Tomohiro; Matsuyama, Yukihiro
Abstract Objective. The aim of the present study was to investigate the efficacy of arthroscopic enlargement of unidirectional valvular slits for the treatment of popliteal cysts and to evaluate potential factors affecting the outcomes of our arthroscopic procedure. Methods. Twenty-nine patients aged 43–77 years with popliteal cysts were treated with arthroscopic cyst decompression. Surgery was performed via two posterior portals after creating a transseptal portal. Rauschning and Lindgren clinical score, magnetic resonance images, and osteoarthritic grade were evaluated pre- and postoperatively, and cartilage degeneration class was confirmed via arthroscopy. The mean follow-up period was 22.9 ± 14.6 months (range, 9–60 months). Results. Twelve cysts disappeared completely (group D), while 16 reduced and one enlarged (group R) in size by the final follow-up. Twenty-two (75.9%) of 29 popliteal cysts diminished to a volume that was less than 10% of the preoperative volume. Clinical scores improved in 93.1% of the patients, and more patients (68.8%) in group R had positive joint effusion at the final follow-up compared with group D (17.7%; p < 0.01). Conclusions. Arthroscopic cyst decompression was effective in the treatment of symptomatic popliteal cysts. Intra-articular pathologies associated with joint effusion should be corrected simultaneously.